Acute and chronic toxicity of deltamethrin, permethrin, and dihaloacetylated heterocyclic pyrethroids in mice. Issue 12 (14th August 2020) - Zhu, Qiuyan; Yang, Yang; Lao, Zhiting; Zhong, Yingying; Zhang, Kun; Zhao, Suqing
Abstract: BACKGROUND: Pyrethroids, a class of insecticides, that act on the nervous system of insects. Frequent consumption of foods with pyrethroid residues increase the risk of developmental and neurological diseases in humans. Assessing the toxicity of novel synthetic pyrethroids to mammals is also critical to the development of agrochemicals. RESULTS: Using mice as models, the acute and chronic toxicity of deltamethrin, permethrin, dihaloacetylated pyrethroids to mammals was researched by gavage administration. Acute toxicity assessment displayed that the median lethal dose (LD50 ) of deltamethrin, permethrin and dihaloacetylated heterocyclic pyrethroids DCA‐O, DCA‐01, and DCA‐11 tested were greater than 500 mg/kg of weight. Furthermore, chronic toxicity assessment demonstrated that deltamethrin, permethrin caused epidermal damage near the genitals, while dihaloacetylated heterocyclic pyrethroids DCA‐O, DCA‐01, and DCA‐11 showed no relevant symptoms. However, both the acute and chronic toxicity assessment suggested that pyrethroids exposure induced mice loss weight. Additionally, the elevated plus maze (EPM) test showed that pyrethroids caused anxiety‐like behaviors and no motor defects in Kunming mice. Beside, during the sucrose preference test (SPT), 60‐day pyrethroids exposure increased excitatory behaviors in mice. However, the neurochemical studies displayed that pyrethroids exposure increased the total amount of glutamate (Gln), glutamine (Glu) and γ ‐aminobutyric acid (GABA) in the mice's blood. CONCLUSION: Pyrethroids exposure induced weight loss in mice, although the acute oral toxicity of deltamethrin, permethrin and dihaloacetylated heterocyclic pyrethroids DCA‐O, DCA‐01, and DCA‐11 was low. However, regarding chronic toxicity, deltamethrin, permethrin and dihaloacetylated heterocyclic pyrethroids DCA‐O, DCA‐01, and DCA‐11 induced anxiety‐like behaviors, excitatory behaviors, Gln‐Glu‐GABA circulatory dysfunction in blood. Particularly, deltamethrin, though permethrin also had reproductive toxicity. © 2020 Society of Chemical Industry Abstract : The acute oral toxicity of analytes (LD50  > 500 mg/kg of weight) is low toxic. But they cause chronic toxicity like anxiety‐like behaviors, excitatory behaviors, neurotoxicity, reproductive toxicity, etc .